Pembentukan Karakter Siswa melalui Pendidikan Al Qur’an - Abu Bakar (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2022)
The more souls exploring the Quran, the less souls will be lost to focus on the Quran. For this reason, learning information about the Quran should be provided for all two studies from early childhood to maturity. On the other hand, the character training currently being promoted and created by the public sector focuses on ethical and high-quality behavioral patterns. The formation of this character emerges and emerges in response to advances in pedagogy (teaching), naturalism, and instrumentalism. The Al Qur'an, which now generally covers all areas of life, including training to decipher by focusing on the Qur'an, means working on each child's own personality. Madrasa Diniyah specialty to learn more in his way emphasizes the strict display of meetings as well as the Quran training, and as an example of undergraduate relationships, they are now attributed to personality training. It focuses on one of the habits of everyday life. For this reason, the author initially expects the character's lessons to be the use of training from the Koran. This has progressed to this point.